Pendampingan Penguatan Budaya Akademik Islami Berbasis Kepemimpinan Transformasional di IAIN Sultan Amai Gorontalo - Pitriyani Mobiliu; Arten Mobonggi; Suleman Kadir (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
The strengthening of Islamic academic culture was required so that quality in Islamic higher education was not only based on administrative targets but also on the institutional internalization of Islamic values. This community service program was conducted to improve the understanding of educational staff regarding Islamic academic culture based on transformational leadership at IAIN Sultan Amai Gorontalo. A participatory method was applied through socialization, discussion, and simple evaluation involving 15 educational staff members. The materials were focused on transformational leadership, Islamic academic culture, trustworthiness, service integrity, and academic quality. The evaluation showed that participants’ understanding increased from a pre-test score of 49.5 to a post-test score of 75.5, representing a 52.5% improvement. The highest increase was found in understanding the relationship between work culture and academic quality at 57.8%. Feedback showed that 86.7% found the material understandable, 93.3% were ready to apply trustworthiness and integrity, and 86.7% supported follow-up activities.